Valve-sparing root reimplantation in patients with left ventricular dilation. (21st July 2022) - Patrick, William L; Rosen, Jake L; Bavaria, Joseph E; Ahmed, Sania; Freas, Andrew; Yarlagadda, Siddharth; Cannon, Brittany; Iyengar, Amit; Kelly, John J; Zhao, Yu; Grimm, Joshua C; Szeto, Wilson Y; et al.
Abstract: OBJECTIVES: The purpose of this study was to evaluate the association between left ventricular (LV) dilation and outcomes following valve-sparing root reimplantation. METHODS: Patients with an indexed LV internal diameter during systole of ≥2.0 cm/m 2 were categorized as having LV dilation. Outcomes were postoperative aortic insufficiency (AI), reintervention and all-cause mortality. The cumulative incidence of each outcome was computed using the Kaplan–Meier estimator. Adjusted comparisons between strata were performed for each outcome using a Cox proportional-hazards model. Where possible, the competing risk of death was accounted for. Multilevel mixed-effects ordered logistic regression was performed for AI grade at follow-up. RESULTS: There were 295 patients of whom 52 had LV dilation. Operative outcomes were excellent; there were no significant differences between groups. Patients with LV dilation demonstrated significant improvement in indexed LV internal diameter during systole overtime. There was no association between LV dilation and postoperative AI grade >2 [hazard ratio 0.88, 95% confidence interval (CI) 0.21–3.67, P  = 0.89] or odds of increased AI grade overtime (odds ratio = 0.76, 95% CI 0.30–1.93, P  = 0.57). There were no re-interventions among those with LV dilation. Adjusted mortality was significantly higher among those with LV dilation (hazard ratio 5.56, 95% CI 1.56–19.9); however, deaths were unrelated to aortic valve dilation. CONCLUSIONS: LV dilation is not associated with poorer operative outcomes, postoperative AI or reintervention. It is associated with an increased risk of mortality, though not from valvular dysfunction. LV dilation should not deter valve-sparing root reimplantation when otherwise indicated. Abstract : Valve-sparing root reimplantation (VSRR) has become a standard alternative to aortic root replacement in select patients, providing a durable repair that obviates the need for anticoagulation [1, 2].